Promoting health information system in guiding decisions for improving performance: an intervention study at the Research Institute of Ophthalmology, Giza, Egypt - Abdelgawad, Yara H; Abd El Razik, Madiha Said; Saleh, Doa’a A; Abuelela, Manal H; Salem, Marwa Rashad (Frontiers in Digital Health, 2024)
Objectives: Design and test a platform of key performance indicators and indices emphasizing achievements, improvement and help decision making. Methods: Operations research study was designed to work on the Hospital Management Information System (HMIS) data for the year July 2017- June 2018 in Research Institute of Ophthalmology (RIO). The available data of HMIS was submitted to reform covering parameters in service delivery and corresponding indicators and indices. It was grouped into 4 themes: human resources, outpatient, inpatient and surgical operations. The total performance indicators were 14 indicators that deployed to four specific indices and total performance index and applied to six teams of RIO. Decision matrices were deliberated to illustrate achievements and recommendations for subsequent improvements. Results: Throughout one year, RIO six teams of ophthalmologists (n=222) provided services: outpatient (n=116043), inpatient (n=8081) and Surgical operations (n=9174.Teams 2, 1 and 6 were the top teams in the total performance index. Team 4 had plunges in outpatient index and team 5 had limitations in the inpatient index. Conclusion: The study provided a model for upgrading the performance of the Management Information System (MIS) in health organizations. Key performance indicators and indices were used for documenting successful models of efficient service delivery, but also as examples of limitations for further support and interventions.